1976
DOI: 10.1111/j.1151-2916.1976.tb09386.x
|View full text |Cite
|
Sign up to set email alerts
|

Fracture Toughness of Al2O3 with an Unstabilized ZrO2Dispersed Phase

Abstract: Keramische Werkstoffe konnen durch Einlagerungen verstarkt bzw. zaher gemacht werden (1)(2)(3)(4)(5)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
138
0
2

Year Published

2000
2000
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 588 publications
(145 citation statements)
references
References 11 publications
5
138
0
2
Order By: Relevance
“…The obtained results support definitively this theoretical prediction. This is of course only true if strong chemical bonding occurs between alumina and zirconia particles and if no microcracks are present after processing, which is the case of 10 vol% zirconia composites [20]. It has been shown that this zirconia content corresponds to a maximum toughening [20].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The obtained results support definitively this theoretical prediction. This is of course only true if strong chemical bonding occurs between alumina and zirconia particles and if no microcracks are present after processing, which is the case of 10 vol% zirconia composites [20]. It has been shown that this zirconia content corresponds to a maximum toughening [20].…”
Section: Resultsmentioning
confidence: 99%
“…7). Thus, it is possible to obtain nano-sized particles in the range from the critical size for spontaneous transformation after sintering, D c ; (above which there is no reinforcement) to the critical size for transformation during crack growth, D 0 c ; (below which there is no crack induced transformation, thus no reinforcement) [20,[31][32][33]. Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The incorporation of zirconia (ZrO 2 ) inclusions into oxide ceramics, especially into alumina matrixes, to deliberately toughen them was undertaken shortly thereafter. 2 The mechanisms by which zirconia acts to toughen the composites are complementary: [3][4][5][6][7] they include transformation toughening, microcracking, and deflection. ZTA composites with high transformation toughening can be obtained if a high portion of tetragonal phase with the ability to transform under applied stress is retained at room temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Objetivando obter tenacidade máxima, a fração volumétrica de inclusões de zircônia deve estar em um nível ótimo, de acordo com Claussen (39) . Segundo o mesmo autor, a tenacidade atinge um valor máximo, e a partir daí, as microtrincas geradas pelas partículas de zircônia irão interagir umas com as outras resultando um decréscimo da resistência.…”
Section: Microtrincamentounclassified